Phragmipedium (Pfitz.) Rolfe - Pupulin, Franco (2020)
The nomenclature of the tropical American lady-slippers has been somewhat confused. At first, the species were named as species of Cypripedium, a name now used only for a north temperate group of terrestrial species. Then they were named as Selenipedium, a group now limited to a few tall, small flowered tropical American species (not known from Costa Rica). Finally, the name Phragmipedium (sometimes spelled Phragmipedilum) was proposed by Rolfe. There are 15 or 20 species in Tropical America, with only two species and their hybrid known in Costa Rica